ANALYSIS OF SEIZURES IN PATIENTS WITH MOTHERS HAVING A HISTORY OF Toxoplasma gondii INFECTION - Nurdianto, Arif Rahman; Apsari, Francisca Cindy Meilia; Safira, Adelia; Hardiwan, Hanalda Wanda (Universitas Airlangga, 2024)
Toxoplasmosis is a disease caused by the parasite Toxoplasma gondii, with high prevalence in Southeast Asia, including Indonesia. This infection can cause brain damage and is associated with diseases such as epilepsy. This study aims to analyze the occurrence of seizures in patients whose mothers have a history of T. gondii infection. Toxoplasmosis during pregnancy can be transmitted to the fetus via the placenta, causing severe fetal tissue damage and potentially triggering neurological disorders like epilepsy. Pathophysiological mechanisms include increased blood-brain barrier permeability, excitotoxicity, and damage to glutamatergic receptors and mitochondria. In Indonesia, the prevalence of toxoplasmosis ranges from 40%-60%, with risk factors including contact with stray cats and consuming raw meat. This study utilizes a literature review method to investigate the relationship between maternal T. gondii infection and the incidence of epilepsy in offspring. The findings suggest that maternal T. gondii infection during pregnancy significantly increases the risk of epilepsy in offspring. Effective public health measures are crucial for raising prevention awareness and improving access to comprehensive prenatal care.